PT. Spektrum Kreasi Pratama's Marketing Communication Strategy in Building Value Creation Through Personal Selling (Case Study of Dr. Ainun Habibie Regional Hospital, Parepare City) - Maddi, Jaenal Hasyim; Lusianawati, Hayu (The Eastasouth Journal of Information System and Computer Science, 2025)
In an era of increasingly fierce business competition, companies must be able to design effective marketing communication strategies, especially in the service sector, such as healthcare services. One approach that is still relevant and effective is personal selling, which allows companies to build long-term relationships with clients through direct communication. This study examines PT. Spektrum Kreasi Pratama's marketing communication strategy in creating value through personal selling, with a focus on Dr. Ainun Habibie Regional Hospital in Parepare City. This study aims to analyze the influence of personal selling strategies in creating value creation, identify the challenges faced in its implementation, and explore how this strategy influences the hospital's decision to choose PT. Spektrum Kreasi Pratama as a partner for medical equipment calibration services. This study uses a descriptive approach with data collection techniques through in-depth interviews, participatory observation, and documentation. The results of the study indicate that personal selling plays an important role in building stronger relationships, increasing trust, and strengthening customer loyalty. However, communication challenges and market competition are obstacles that need to be overcome. This study concludes that personal selling is key to creating sustainable value creation and facilitating a successful partnership between PT. Spektrum Kreasi Pratama and healthcare institutions.